З історії одного вчительського листа - Нестеренко, Л. (Сiверянський лiтопис, 2018)
На основі архівних джерел у статті показано трагедію життя трьох учителів
Горобіївської неповної середньої школи Срібнянського району Чернігівської області Якова Спиридоновича Момота, Ілька Івановича Падалки і Єфрема Семеновича Неділька,
які, незважаючи на всі репресивні дії радянської влади проти українців у 20–30-х рр.
минулого століття, не побоялися відкрито говорити правду про справжню радянську
дійсність. У серпні 1940 р. вони написали до Голови Президії Верховної Ради СРСР
М. І. Калініна листа, в якому описали тяжке та голодне життя українського селянства
та сільської інтелігенції. 23 липня 1941 р. Військовий трибунал військ НКВС Київської
області в м. Чернігові виніс вирок обвинуваченим. Кожного із учителів було позбавлено
волі терміном на 10 років, з відбуванням покарання у трудових таборах, а також
кожного позбавлено громадських прав терміном на п’ять років. На основании обработанных архивных источников, в статье показано трагедию
жизни трёх учителей Горобиевской неполной средней школы Сребнянского района
Черниговской области Я. С. Момота, И. И. Падалки и Е. С. Недилька, которые, не
взирая на репрессии советской власти против украинцев в 30-х гг. ХХ в., говорили
правду о настоящей советской действительности. В 1940 г. они написали письмо на
имя Председателя Президиума Верховного Совета СССР М. И. Калинина. В своём
обращении учителя описали условия жизни украинского крестьянства и сельской
интеллигенции в настоящее время. 23 июля 1941 г. Военный трибунал войск НКВД
Киевской области в г. Чернигове приговорил всех троих подвергнуть лишению свободы сроком на 10 лет каждого и поражением в правах на пять лет каждого. On the basis of archive sources in the article, the life tragedy of three teachers of the
Gorobiev incomplete secondary school of Sribnyansky district of Chernihiv region, Yakov
Spyrydonovych Momot, Ilko Ivanovych Padalka and Yefrema Semenovych Nedilka is shown.
These people, despite all the repressive actions of Soviet government against the Ukrainians in
the 20-30’s of the last century were not afraid to speak truth about true Soviet reality openly
among students, colleagues and fellow-villagers.
In August 1940, they wrote a letter to the Chairman of Presidium of the Supreme Soviet
of the USSR M.I. Kalinin. In this letter, teachers described the hard and hungry life of the
Ukrainian peasantry and the rural intelligentsia. The authors also pointed out that more
than 2 million people died in the Holodomor of 1932-1933 in Ukraine, and also described the
extremely difficult situation in Ukraine in 1939-1940, which barely grew into a new wave
of famine. For this, on July 23, 1941, the Military Tribunal of the NKVD of Kyiv region in
Chernihiv sentenced the accused. Each of the teachers was deprived of his liberty for a term
of 10 years, with the imprisonment in labor camps, and everyone was deprived of public rights
for a term of five years.
The article also explores the further life of Nedilka Ye.S., who in 1962 wrote a letter to
the Supreme Court of the USSR. In his letter, the teacher briefly described the reason for his
imprisonment and asked for reconsidering his criminal case and his rehabilitation. However,
his application was rejected. Only on the day of independence of Ukraine, namely September
26, 1991, all three teachers were finally rehabilitated.